An anonymity mechanism with reduced server-side cost in peer-to-peer networks. (2016) - Peng, Hao; Zhao, Dandan; Han, Jianmin; Lu, Jianfeng
In peer-to-peer (P2P) networks, each peer's trustworthiness is evaluated according to its pseudonym's rating values given by other peers. One of the fundamental challenges in peer-to-peer networks is to protect peers' identity privacy on the communication path. In this paper, we present an anonymity mechanism to achieve all the peers' anonymity in peer-to-peer networks by changing pseudonyms with the help of a trusted third party (TTP) server. Compared with the existing reputation using pseudonyms (RuP) mechanism, our mechanism has reduced TTP server's cost by more than 50% in terms of numbers of RSA and AES decryption operations and message overhead. Simulation results show the effectiveness of our proposed anonymity mechanism to counter malicious peers.